Molecular and phenotypical investigation of ciprofloxacin resistance among Campylobacter jejuni strains of human origin: high prevalence of resistance in Turkey - Ilktac, Mehmet; Ongen, Betigul; Humphrey, Thomas J.; Williams, Lisa K. (Wiley, 2020)
Campylobacteriosis is one of the most frequently reported zoonoses worldwide. The well-documented increase in the ciprofloxacin resistance has increased the importance of rapid detection of the resistance. The incidence of ciprofloxacin resistance was investigated using real-time PCR. Identification of one hundred and fifty-eight strains was performed by PCR. Minimum inhibitory concentration (MIC) of ciprofloxacin was determined by Epsilometer test. Following the confirmation of the efficiencies of singleplex real-time PCR methods using two different probes, a cytosine to thymine point mutation at codon 86 was detected by allelic discrimination. Of the 158 strains, 114 (72.2%) were determined to be resistant to ciprofloxacin. The MIC50 and the MIC90 of ciprofloxacin were found to be 8 and >= 32 mg/L, respectively. By real-time PCR, the presence of the mutation was confirmed in all, but one, resistant strains and the absence of the mutation was demonstrated in all, but one, susceptible strains. The rate of resistance is high among C. jejuni strains and ciprofloxacin should not be used in the treatment of such infections in Turkey. A cytosine to thymine mutation is the most frequently detected mechanism for the resistance. Real-time PCR can be used for the quick screening of the resistance.
Keywords: Campylobacter; ciprofloxacin; E-test; real-time PCR; resistance; Turkish